2017
DOI: 10.1016/j.antiviral.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

The role of epidermal growth factor receptor (EGFR) signaling in SARS coronavirus-induced pulmonary fibrosis

Abstract: Many survivors of the 2003 outbreak of severe acute respiratory syndrome (SARS) developed residual pulmonary fibrosis with increased severity seen in older patients. Autopsies of patients that died from SARS also showed fibrosis to varying extents. Pulmonary fibrosis can be occasionally seen as a consequence to several respiratory viral infections but is much more common after a SARS coronavirus (SARS-CoV) infection. Given the threat of future outbreaks of severe coronavirus disease, including Middle East resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
174
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(183 citation statements)
references
References 91 publications
5
174
0
4
Order By: Relevance
“…In 2002, a case of SARS appeared in Guangdong Province, China, and then spread to Southeast Asia and all of the world [6] . The SARS outbreak comprehensively All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2002, a case of SARS appeared in Guangdong Province, China, and then spread to Southeast Asia and all of the world [6] . The SARS outbreak comprehensively All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…Age and comorbidities (such as diabetes or heart disease) are independent predictors of poor SARS-CoV and MERS-CoV outcomes. The spread of SARS-CoV and MERS-CoV occurred to a large extent through super-transmission events [6][7] .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that TGF-␤ is an antiinflammatory cytokine that can induce fibrogenesis. More recently, it has been suggested that pulmonary fibrosis in SARS-CoV is caused by a hyperactive host response to lung injury mediated by epidermal growth factor receptor (EGFR) signalling [20]. Inhibiting EGFR signalling, by the use of tyrosine kinase inhibitors like nintedanib, a drug licensed for idiopathic lung fibrosis, seems promising for interstitial lung disease in systemic sclerosis [21], and might also be useful for COVID-19.…”
Section: Lung Damage and Fibrosismentioning
confidence: 99%
“…Signaling through the IL‐15 receptor is known to be important in the development . Recent studies showed that JAK‐STAT signaling play an important role in the pathogenesis of pulmonary fibrosis, and thus inhibition JAK‐STAT signaling in fibroblasts may be effective in the treatment of fibrosis . Bruton's tyrosine kinase (BTK) is a type of kinase protein expressed in B lymphocytes and T cells .…”
Section: Figurementioning
confidence: 99%
“…[17,18] Recent studies showed that JAK-STAT signaling play an important role in the pathogenesis of pulmonary fibrosis, and thus inhibition JAK-STAT signaling in fibroblasts may be effective in the treatment of fibrosis. [19][20][21][22] Bruton's tyrosine kinase (BTK) is a type of kinase protein expressed in B lymphocytes and T cells. [23] BTK deficiency in humans is associated with reduction in TNF-α production by activated monocytes.…”
Section: Novel Pyrimidines As Multitarget Protein Tyrosine Kinase Inhmentioning
confidence: 99%